2020
DOI: 10.23822/eurannaci.1764-1489.109
|View full text |Cite
|
Sign up to set email alerts
|

Severe CSU and activation of the coagulation/fibrinolysis system: clinical aspects

Abstract: Background. About 50% of patients with severe chronic spontaneous urticaria (CSU) show signs of activation of the coagulation/fibrinolysis system, but the clinical significance of this phenomenon is unclear. Objective. The present study compared patients with severe CSU showing and not showing elevated D-dimer plasma levels. Methods. 132 adult patients (m/f 44/88; mean age 51, 5 years; range 14-89 years) with severe CSU (UAS-7 > 30) were included in a cross-sectional, real life study. The study group was divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(23 reference statements)
0
7
1
Order By: Relevance
“…Recent reports [31][32][33][34][35] suggest that additional endotypes of CSU may exist, with evidence pointing to a role of factors of the coagulation pathway, ligands of the MASrelated G protein-coupled receptor X2 (MRGPRX2), ba-sophils, alarmins, and other signals in the pathogenesis of CSU. More research is needed to clarify whether mechanisms of skin MC degranulation other than type I and type IIb autoimmune activation support the existence of distinct and separate endotypes.…”
Section: Type I and Type Iib Autoimmunity: Emerging Endotypes Of Chromentioning
confidence: 99%
“…Recent reports [31][32][33][34][35] suggest that additional endotypes of CSU may exist, with evidence pointing to a role of factors of the coagulation pathway, ligands of the MASrelated G protein-coupled receptor X2 (MRGPRX2), ba-sophils, alarmins, and other signals in the pathogenesis of CSU. More research is needed to clarify whether mechanisms of skin MC degranulation other than type I and type IIb autoimmune activation support the existence of distinct and separate endotypes.…”
Section: Type I and Type Iib Autoimmunity: Emerging Endotypes Of Chromentioning
confidence: 99%
“…27 On the other hand, Asero et al suggested that D-dimer levels are elevated in severe cases of CSU, but this elevation varies among individuals, attributed to distinct underlying mechanisms. 28,29 Similar to D-dimer, elevated fibrinogen levels were also observed in CSU. 15 Albumin acts as a negative acute phase reactant, and new studies emphasize that it can also function in both procoagulant and anticoagulant mechanisms.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, Asero et al. suggested that D‐dimer levels are elevated in severe cases of CSU, but this elevation varies among individuals, attributed to distinct underlying mechanisms 28,29 . Similar to D‐dimer, elevated fibrinogen levels were also observed in CSU 15 …”
Section: Discussionmentioning
confidence: 99%
“…CSU patients that take more than a month (late responders) to respond to omalizumab, probably underwent a type IIb autoimmunity, where the reduction of free IgE results in the slow loss of membrane-bound FcεRI from skin mast cells [46]. New endotypes of CSU have been proposed in addiction by recent reports, suggesting a key role of the coagulation pathway factors, ligands of the Mas-related G protein-coupled receptor X2, basophils, and other signals in the pathogenesis of CSU [47,48]. Moreover, other research to characterize better the role and the relevance of type I and type IIb autoimmunity in CSU and to support the existence of distinct and separate endotypes, are still in progress.…”
Section: The Chronic Spontaneous Urticaria Main Endotypesmentioning
confidence: 99%